Average
MCQs Math


Question:     Find the average of even numbers from 6 to 986


Correct Answer  496

Solution And Explanation

Solution

Method (1) to find the average of the even numbers from 6 to 986

Shortcut Trick to find the average of the given continuous even numbers

The even numbers from 6 to 986 are

6, 8, 10, . . . . 986

After observing the above list of the even numbers from 6 to 986 we find that the difference between two consecutive terms are equal. This means the list of the even numbers from 6 to 986 form an Arithmetic Series.

In the Arithmetic Series of the even numbers from 6 to 986

The First Term (a) = 6

The Common Difference (d) = 2

And the last term (ℓ) = 986

The average of the numbers forming an Arithmetic Series

= The first term (a) + The last term (ℓ)/2

⇒ The average of numbers forming an Arithmetic Series = a + ℓ/2

Thus, the average of the even numbers from 6 to 986

= 6 + 986/2

= 992/2 = 496

Thus, the average of the even numbers from 6 to 986 = 496 Answer

Method (2) to find the average of the even numbers from 6 to 986

Finding the average of given continuous even numbers after finding their sum

The even numbers from 6 to 986 are

6, 8, 10, . . . . 986

The even numbers from 6 to 986 form an Arithmetic Series in which

The First Term (a) = 6

The Common Difference (d) = 2

And the last term (ℓ) = 986

The Average of the given numbers

= Sum of the given numbers/Total number of given numbers

Thus, to find the average of the given numbers, first, we need to find their sum and the total number of given numbers

Finding the number of terms

For an Arithmetic Series, the nth term

an = a + (n – 1) d

Where

a = First term

d = Common difference

n = number of terms

an = nth term

Thus, for the given series of the even numbers from 6 to 986

986 = 6 + (n – 1) × 2

⇒ 986 = 6 + 2 n – 2

⇒ 986 = 6 – 2 + 2 n

⇒ 986 = 4 + 2 n

After transposing 4 to LHS

⇒ 986 – 4 = 2 n

⇒ 982 = 2 n

After rearranging the above expression

⇒ 2 n = 982

After transposing 2 to RHS

⇒ n = 982/2

⇒ n = 491

Thus, the number of terms of even numbers from 6 to 986 = 491

This means 986 is the 491th term.

Finding the sum of the given even numbers from 6 to 986

The sum of all terms (S) in an Arithmetic Series

= n/2 (a + ℓ)

Where, n = number of terms

a = First term

And, ℓ = Last term

Thus, the sum of all terms (S) of the given even numbers from 6 to 986

= 491/2 (6 + 986)

= 491/2 × 992

= 491 × 992/2

= 487072/2 = 243536

Thus, the sum of all terms of the given even numbers from 6 to 986 = 243536

And, the total number of terms = 491

Since, the average of the given numbers

= Sum of the given numbers/Total number of given numbers

Thus, the average of the given even numbers from 6 to 986

= 243536/491 = 496

Thus, the average of the given even numbers from 6 to 986 = 496 Answer


Similar Questions

(1) What is the average of the first 623 even numbers?

(2) Find the average of even numbers from 6 to 1474

(3) Find the average of even numbers from 8 to 1392

(4) Find the average of even numbers from 12 to 530

(5) Find the average of the first 3117 even numbers.

(6) Find the average of even numbers from 6 to 572

(7) Find the average of odd numbers from 13 to 855

(8) Find the average of even numbers from 10 to 1010

(9) Find the average of the first 1647 odd numbers.

(10) Find the average of even numbers from 4 to 1508


NCERT Solution and CBSE Notes for class twelve, eleventh, tenth, ninth, seventh, sixth, fifth, fourth and General Math for competitive Exams. ©